(3GSGdjH GdJMdjd GdGMUGFj HGSJNOGe HQeLjI (BSPSS /s - (3GHhGdRjO, eMeO NjQs ((3YeGf(B: s (3OGQ LQjQ ddfTQ hGdJhRjY(B, s, 2005)
(3GdGSJHGfI(B, (3CfhGY GdebGjjS(B, (3GdJQejR GVGaI Gdi bGFeI (Bvariable view, (3GdJYGed eY eda GdHjGfGJ h JMQjQgG(B, (3bGFeI (BData, (3bGFeI (BTransfofm (3cPdc GdGMUGA GdhUaj h cPG GNJHGQ GdaQVjGJ(B, (3GNJHGQ GdYjfI GdGMGOjI(B, (3GNJHGQ ebGQfI Hjf YjfJjf(B, (3GNJHGQ cGj SchjQ(B, (3JMdjd GdJHGjf GdGMGOj(B, (3JMdjd GdJHGjf GdKfGFi(B, (3GdGQJHGW h GdGfMOGQ GdHSjW h GdeJYOO(B, (3YQV GdHjGfGJ (B- (3GdGTcGd GdHjGfjI h aj GdGNjQ YQV MGdI YdejI(B.s
(3eQGLY U(B.219s
Keywords: (3GdJMdjd GdGMUGFjs; (3GdMhGSjHs